KONVERSI ENERGI ANGIN MENJADI ENERGI LISTRIK DALAM SKALA LABORATORIUM - Febrielviyanti '; Maksi Ginting; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The convertion of wind energy into electrical energy in laboratory is experimentally conducted, to the source of the wind came from the fan, which then flowed into a tunnel. The generator used is bicycle dynamo with voltage output of 12 Volt. The wind speed against the tunnel lenght increases when the length are 0,90 m, 0,75 m, and 0,60 m, and decrease on 0,45 m and 0,30 m. The decrease of wind speed occur because of fan vibration, unregularity of tunnel surface area and turbulence. The wind speed is observed to be the largest on the length of 0,60 m with the wind speed at the level of the third button of fan its average speed of 4,16 m/s with generator power, torque and efficiency are 9,47× 10−3 Watt, 2,63× 10−1 Nm and 0,30% respectively. The current and voltage output produced by generator is AC current and voltage and resulte 72,85 mA dan 0,13 Volt, therefore to convert they into DC current and voltage output, effective current and voltage equation is applied which get 0,05 Ampere and 0,09 Volt.